Is Central Bank Intervention Effective Under Inflation Targeting Regimes? : The Case of Colombia - Kamil, Herman (IMF Working Papers; Working Paper ;, 2008)
Policymakers in many emerging markets are attempting to resist currency appreciation while simultaneously meeting targets for inflation. Using the recent experience of Colombia between 2004 and 2007, this paper examines the effectiveness of the Central Bank's intervention in stemming domestic currency appreciation under an inflation targeting regime. The results indicate that exchange rate intervention was effective during 2004-2006, when foreign currency purchases were undertaken during a period of monetary easing. During 2007, on the other hand, intervention was ineffective in reversing or slowing down domestic currency appreciation, as large-scale intervention became incompatible with meeting the inflation target in an overheating economy. Currency derivative markets-which have grown in depth and sophistication-played a key role in blunting the effectiveness of intervention.